PENGGUNAAN BAHAN ALAMI UNTUK PENGURANGAN PESTISIDA SEBAGAI UPAYA MENDUKUNG PENCEGAHAN STUNTING - Giovani, Iqbal; Primasari, Winda; Faiz Ridio, Azi (An-Nizam, 2023)
Community service in cabangbungin district, the village of jayabakti, the village of two village asem to reduce the use of pesticides that will cause stunting by the use of a natural biopesticide. It concerns the people of jayabakti whose main job is farmer with an 87% percentage. Farmersotend to continue to use dangerous chemicalopesticides to eradicatopests, so the production of a biopestier is an answer to reducing the use of dangerous chemical pesticides in view of the effects of the useoof chemicalopesticides that are harmful to both human and environmental health. Based on these issues, we had an idea to provide solutions through socialization and practice. Based on the activity of "the use of natural materials for pesticide reduction in support of stunting prevention" it can conclude that the results of this community's devoted activity have a positive impact, with those who present in the quest for knowledge and information on natural materials being used asa biopestimatic weathering against the plants. A partial distribution of biopestiles to the plant and a filling out questionnaire, whichomeans that the purposeoof this activity is to divertothe use of the pesticide to a successful extent.